Characterization of ndh gene of isoniazid resistant and susceptible Mycobacterium tuberculosis isolates from Brazil - Cardoso, Rosilene Fressatti; Cardoso, Marco Antonio; Leite, Clarice Queico Fujimura [UNESP]; Sato, Daisy Nakamura; Mamizuka, Elsa Masae; Hirata, Rosário Dominguez Crespo; Mello, Fernando Fiúza de; Hirata, Mario Hiroyuki (Instituto Oswaldo Cruz, Ministério da Saúde, 2007)
Resistance in Mycobacterium tuberculosis to isoniazid (INH) is caused by mutations in the catalase-peroxidase gene (katG) , and within the inhA promoter and/or in structural gene. A small percentage (~ 10%) of INH-resistant strains do not present mutations in both of these loci. Other genes have been associated with INH resistance including the gene encoding for NADH dehydrogenase (ndh) . Here we report the detection of two ndh locus mutations (CGT to TGT change in codon 13 and GTG to GCG change in codon 18) by analyzing 23 INH-resistant and in none of 13 susceptible isolates from Brazilian tuberculosis patients. We also detected two isolates without a mutation in ndh, or any of the other INH resistance-associated loci examined, suggesting the existence of additional, as yet to be described, INH resistance mechanisms.
Keywords: Mycobacterium tuberculosis; NADH dehydrogenase gene; isoniazid resistance